2012
DOI: 10.2174/138527212799859390
|View full text |Cite
|
Sign up to set email alerts
|

Strategies and Methods for the Syntheses of Natural Oligomeric Stilbenoids and Analogues

Abstract: This review covers synthetic work carried out in the field of stilbene and oligostilbene chemistry. It includes a brief overview of the methods used for the synthesis of monomeric stilbenoids. The production of oligomeric species by means of enzymatic or microbial conversion is examined in detail. Biomimetic syntheses of stilbene oligomers are then scrutinised. Most of the work is based on the dimerisation of stilbenoid monomers with help of one-electron oxidants or through acid catalysis. Mechanistic interpre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(3 citation statements)
references
References 121 publications
(209 reference statements)
0
3
0
Order By: Relevance
“…As stilbenoids are known to form dimers and polymers with a variety of acids, including BBr 3 [34,35], alternative protocols were investigated. We first attempted to obtain the desired compound 19 by the initial deprotection of bromoderivative 8, followed by a direct insertion of the p-hydroxystyryl moiety via the Heck reaction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As stilbenoids are known to form dimers and polymers with a variety of acids, including BBr 3 [34,35], alternative protocols were investigated. We first attempted to obtain the desired compound 19 by the initial deprotection of bromoderivative 8, followed by a direct insertion of the p-hydroxystyryl moiety via the Heck reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, attempts to deprotect the methyl groups with BBr 3 at −78 • C in dry DCM, following the usual procedure, gave only degradation products.Several troublesome efforts in the demethylation process confirmed that this step is an Achilles' heel in the synthesis of stilbenoids-derived compounds[6,10,14,22].Methyl groups are convenient protecting groups for phenolic moieties because of the availability of their starting reagents and their high stability to a wide variety of reaction conditions. However, as a not-negligible drawback, their high robustness requires harsh conditions in the deprotection step, often resulting in poor yields and product degradation in the presence of highly reactive double bonds[5,6,10,22].As stilbenoids are known to form dimers and polymers with a variety of acids, including BBr 3[34,35], alternative protocols were investigated. We first attempted to obtain the desired compound 19 by the initial deprotection of bromoderivative 8, followed by a direct insertion of the p-hydroxystyryl moiety via the Heck reaction.…”
mentioning
confidence: 99%
“…A comparatively high amount of resveratrol can be produced by chemical synthesis, but it suffers from the formation of many unwanted side products that contaminate the resveratrol and make purifying it complicated. Thus there is a high risk in using such resveratrol as medicines and food ingredients [62,63,64]. Different biotechnological approaches, such as tissue culture and genetic engineering, have been applied as alternative bio-sustainable resources to produce resveratrol.…”
Section: Biological Significance In Humansmentioning
confidence: 99%